Impact assessment of food policy research -- a stocktaking workshop: synthesis report - Anderson, Jock R.; Bos, Maria Soledad; Cohen, Marc J. (International Food Policy Research Institute, 2005)
This stocktaking workshop provided an opportunity for several groups with active interest in impact assessment relating to agricultural policy research to share experiences and views about what constitutes good practice in this field. The sponsoring organizations have had a long-standing concern for the relevance and effectiveness of agricultural and food policy research in general and at IFPRI in particular. That concern has been addressed in past meetings and the time seemed right for a further stocktaking. The focus of this 2004 meeting was on impact assessment experience at IFPRI. IFPRI has, since the mid-1990s, carried out a variety of activities aimed at assessing the impact of its policy research, capacity strengthening, and policy communications programs. The workshop brought together practitioners of such impact assessment work, users of such information, as well as researchers whose activities have been the subject of impact assessment. The cogency and necessity of such impact accounting work was reaffirmed in general terms. There was constructively critical commentary on the merits of particular approaches and instruments, such as narrative recordings and more quantitative methods of attempting to measure effects of research investments. The perennial issue of challenging counterfactuals was necessarily addressed, and the practicality of experimental and quasi-experimental methods considered. The need for consistency of assessment approaches between ex post studies (which have been the bulk of IFPRI’s experience to date) and ex ante assessment efforts that represent an increasing share of the assessment portfolio was also discussed. There has long been a commitment to work towards a strong impact-orientation “culture” within IFPRI; the workshop concluded that, while there has been progress in working toward mainstreaming such a culture, there is still far to go, and efforts must continue in this direction.